2009
DOI: 10.1007/s00330-009-1550-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of mean diffusivity (MD) as a predictive index of the response to chemotherapy in locally advanced breast cancer: a preliminary study

Abstract: This preliminary study seems to indicate that low values of pre-chemotherapy MD may identify, before starting treatment, the patients with higher probability of response in terms of percentage of volume reduction of the lesion. MD may represent a complementary parameter useful to correctly select patients for neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 26 publications
6
39
1
2
Order By: Relevance
“…This finding is in agreement with other studies showing that changes in ADC can be found after only one cycle of NAC, with even a more pronounced increase after two cycles (8,10,33). This result is promising, because the implication is that ADC may be considered as a direct measure of treatment effects to chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with other studies showing that changes in ADC can be found after only one cycle of NAC, with even a more pronounced increase after two cycles (8,10,33). This result is promising, because the implication is that ADC may be considered as a direct measure of treatment effects to chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that for breast cancer patients undergoing neoadjuvant docetaxel/doxorubicin therapy, pretreatment tumor ADC was significantly lower in responders (1.04 × 10 −3 mm 2 /second), defined as patients with greater than 65% reduction in tumor volume after therapy, than in nonresponders (1.30 × 10 −3 mm 2 /second). A similar relationship between pretreatment tumor ADC and tumor volume change was also found by Iacconi et al (10). However, other studies have found no correlation between pretreatment tumor ADC and final tumor volume change or pathologic complete response (4,13,24).…”
Section: Discussionsupporting
confidence: 86%
“…However, no consensus has been reached regarding the value of pretreatment ADC to predict the response to NAC. [17][18][19][20][21][22][23] It is also unclear whether this would be influenced by the tumor phenotype.…”
Section: Introductionmentioning
confidence: 97%